2013
DOI: 10.1260/1369-4332.16.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damage Detection in a Truss Bridge Model Using Fuzzy Clustering and Measured FRF Data Reduced by Principal Component Projection

Abstract: This study deals with vibration-based damage detection in a truss bridge model and suggests a novel methodology based on fuzzy clustering and measured frequency response function (FRF) data reduced by principal component projection. A six-bay truss bridge model is designed and fabricated in laboratory, various connection damages are simulated by loosening the end connecter bolts, and the environmental effects are taken into account by changing in excitation force levels of a shaker. The FRFs of the healthy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Applications involving aging and wearing out of components, processes dealing with seismic signals, are generally time-varying where the signals evolve in real time and the process becomes too complex to be analyzed via a simple offline method (Misra et al 2002;Yu et al 2013;Gharibnezhad et al 2015). In practical SHM scenarios, data streams continuously in real time, which further necessitates that the algorithm should be amenable towards online implementation, independent of any baseline (reference) data.…”
Section: Real Time Single and Multi Channel Structural Damage Detectimentioning
confidence: 99%
“…Applications involving aging and wearing out of components, processes dealing with seismic signals, are generally time-varying where the signals evolve in real time and the process becomes too complex to be analyzed via a simple offline method (Misra et al 2002;Yu et al 2013;Gharibnezhad et al 2015). In practical SHM scenarios, data streams continuously in real time, which further necessitates that the algorithm should be amenable towards online implementation, independent of any baseline (reference) data.…”
Section: Real Time Single and Multi Channel Structural Damage Detectimentioning
confidence: 99%
“…where, ( ) = ith membership function of jth feature, = absolute value, = related mean value (midpoint) and = variance of the jth feature in ith class. In [89], the authors suggested a noteworthy methodology on the basis of fuzzy clustering combined with computed frequency response function samples minimized via principal component projection in order to investigate damage detection in truss bridge model using vibration based technique. The preliminary data utilized in this investigation are the FRFs associated with the healthy as well as the damaged structure.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…The vibration-based SDD technique has become an effective way in SDD [1,2]. Normally, SDD can be achieved by comparing the structural characteristics extracted from structural reference state and damage state respectively.…”
Section: Introductionmentioning
confidence: 99%